Global Surgery Indicators and Pediatric Hydrocephalus: A Multicenter Cross-Country Comparative Study Building the Case for Health System Strengthening - Ferraris, Kevin Paul; Palabyab, Eric Paolo M.; Kim, Sergei; Matsumura, Hideaki; Yap, Maria Eufemia C.; Cloma-Rosales, Venus Oliva; Letyagin, German; Muroi, Ai; Baticulon, Ronnie E.; Alcazaren, Jose Carlos; Seng, Kenny; Navarro, Joseph Erroll (Frontiers in Surgery, 2021)
Objective: The aim of this study is to compare specific three-institution, cross-country data that are relevant to the Global Surgery indicators and the functioning of health systems. Methods: We retrospectively reviewed the clinical and socioeconomic characteristics of pediatric patients who underwent cerebrospinal fluid (CSF) diversion surgery for hydrocephalus in three different centers: the University of Tsukuba Hospital in Ibaraki, Japan (HIC), the Jose R. Reyes Memorial Medical Center in Manila, Philippines [low-to-middle-income country (LMIC)], and the Federal Neurosurgical Center in Novosibirsk, Russia (UMIC). The outcomes of interest were the timing of CSF diversion surgery and mortality. Statistical tests included descriptive statistics, Cox proportional hazards model, and logistic regression. Nation-level data were also obtained to provide the relevant socioeconomic contexts in discussing the results. Results: In total, 159 children were included, where 13 are from Japan, 99 are from the Philippines, and 47 are from the Russian Federation. The median time to surgery at the specific neurosurgical centers was 6 days in the Philippines and 1 day in both Japan and Russia. For the cohort from the Philippines, non-poor patients were more likely to receive CSF diversion surgery at an earlier time (HR = 4.74, 95% CI 2.34–9.61, p <0.001). In the same center, those with infantile or posthemorrhagic hydrocephalus (HR = 3.72, 95% CI 1.70–8.15, p = 0.001) were more likely to receive CSF diversion earlier compared to those with congenital hydrocephalus, and those with postinfectious (HR = 0.39, 95% CI 0.22–0.70, p = 0.002) or myelomeningocele-associated hydrocephalus (HR = 0.46, 95% CI 0.22–0.95, p = 0.037) were less likely to undergo surgery at an earlier time. For Russia, older patients were more likely to receive or require early CSF diversion (HR = 1.07, 95% CI 1.01–1.14, p = 0.035). External ventricular drain (EVD) insertion was found to be associated with mortality (cOR 14.45, 95% CI 1.28–162.97, p = 0.031). Conclusion: In this study, Filipino children underwent late time-interval of CSF diversion surgery and had mortality differences compared to their Japanese and Russian counterparts. These disparities may reflect on the functioning of the health systems of respective countries.